Zoo Benthic Biodiversity as a Bioindicator in the Bengawan Solo Estuary - Qurrota Fu'adah, Elva; Ahmad Shofy Mubarak; Sulistiono; Nina Nurmalia Dewi; Annur Ahadi Abdilah; Prima Almira; Firman Budi Cahyadi; Juni Triastuti (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research Salinity is the critical influencing the distribution of macrobenthos species based on habitat (seawater and freshwater species) in estuaries. The brackish water station exhibited the highest macrobenthos abundance, whereas the seawater station showed the highest meiobenthos abundance. Corresponding water quality parameters markedly influenced the abundance of each benthic group. The calculation of abundance and biological indexes classified the Bengawan Solo estuary as relatively stable.     Abstract As key aquatic organisms, benthos are a reliable indicator of water quality owing to their relatively fixed habitats, limited mobility, and residence at the bottom of the water. This study aimed to analyze benthos’ biodiversity and community structure as bioindicators in the waters of the Bengawan Solo estuary that important for fishery activities conducted by local fishermen community. A descriptive analysis method was employed, involving identifying and analyzing benthos in density, biological indexes, and principal component analysis (PCA). The macrobenthos species composition consisted of Gastropoda, Bivalvia, Maxillopoda, Malacostraca, Polychaeta, and Clitellata while meiobenthos comprised Foraminifera, Bivalvia, Gastropoda, and Polychaeta. Macrobenthos density was 288 ind./m2, whereas meiobenthos density was 16 ind./10 cm2. Both macrobenthos and meiobenthos exhibited a moderate diversity index and a medium evenness index, although evenness values tended to be higher in macrobenthos. The dominance index for both macrobenthos and meiobenthos showed moderate values. PCA analysis revealed that macrobenthos, Bivalvia, Gastropoda, and Clitellata density was influenced by brightness and turbidity, Malacostraca and Maxillopoda density by salinity, and Polychaeta density by dissolved oxygen. In meiobenthos, Gastropoda and Foraminifera density was influenced by salinity, whereas Bivalvia and Polychaeta density was affected by brightness and turbidity. Density and biological index results indicate that the Bengawan Solo estuary is relatively stable.